CRIMINAL LAW REFORM IN THE NEW KUHP: PARADIGM ANALYSIS AND ITS IMPLICATIONS FOR THE JUSTICE SYSTEM - Henny Saida Flora (PT. Anagata Sembagi Education, 2026)
The enactment of Law Number 1 of 2023 concerning the Criminal Code (National Criminal Code) marks a fundamental change in the architecture of Indonesian criminal law after more than a century of being subject to the Wetboek van Strafrecht, a colonial legacy. This article aims to analyze the paradigm shift brought by the National Criminal Code, specifically the shift from a retributive-legalistic paradigm to a paradigm that accommodates the balance of interests of perpetrators, victims, and society through the principle of monodualistic balance, and examines the normative and structural implications of this change for the Indonesian criminal justice system. Beyond mapping these reforms, this article also critically examines the conceptual tensions embedded within this paradigm shift, particularly the unresolved dualism between the recognition of living law and the principle of legal certainty, situating the discussion within Thomas Kuhn’s framework of paradigm change. This research uses a normative juridical method with a statutory, conceptual, and comparative approach. The results of the study indicate that the National Criminal Code introduces a number of significant reform ideas, including the recognition of living law in society as a source of material criminal law, strengthening the principles of subsidiarity and ultimum remedium, the implementation of a two-track system in criminal punishment, the formulation of explicit objectives and guidelines for criminal punishment, and more comprehensive regulations for corporate criminal liability. The implications of this paradigmatic shift for the criminal justice system include the need to adjust criminal procedural law, increase the institutional capacity of law enforcement officials, reorient legal culture toward a restorative justice approach, and the challenge of harmonizing the National Criminal Code with various existing special criminal laws. This article recommends strengthening derivative regulations, intensive training for law enforcement officials, and ongoing implementation oversight to ensure the goals of criminal law reform are achieved effectively and fairly.